EQUILIBRIUM MEASUREMENTS OF EMBRYONIC CHICK CELL ADHESIVENESS, I. SHAPE EQUILIBRIUM IN CENTRIFUGAL FIELDS - Phillips, Herbert M. (1969)
Sorting-out and other morphogenetic rearrangements of embryonic cells have been attributed to the spontaneous movements of mutually adhesive cells toward configurations of minimal adhesive free energy. Testing this hypothesis requires measuring those particular adhesive properties that would determine such equilibrium configurations. We have devised a modification of the sessile drop method for making the required measurements. This communication is a preliminary report of experiments demonstrating that intercellular adhesiveness is reflected in the equilibrium shapes of centrifuged cell aggregates.